A short assessment tool for small vessel disease with cognitive impairment: The Virtual Supermarket (VSM): Developing topics. (7th December 2020) - Boz, Hatice Eraslan; Limoncu, Hatice; Zygouris, Stelios; Tsolaki, Magda; Giakoumis, Dimitris; Votis, Konstantinos; Tzovaras, Dimitris; Öztürk, Vesile; Yener, Görsev
Abstract: Background: Detailed neuropsychological assessment is essential to detect cognitive impairment in SVD. Therefore, a brief cognitive test is needed as an alternative to extensive assessment (Peng et al., 2019). The aim of this study is to examine cognitive functions between SVD with cognitive impairment (SVD‐CI), cognitively normal SVD (SVD‐CN), and healthy controls (HC) using the Virtual Supermarket (VSM) application and whether the VSM correlates the traditional pencil‐and‐paper neuropsychological tests. Method: Thirty‐two SVD‐CI, 37 SVD‐CN and 30 HC were included the study. All participants were applied to virtual reality‐based VSM with tablet and comprehensive neuropsychological tests. (Zygouris et al., 2015; Eraslan‐Boz et al., 2019). Result: SVD‐CI patients were poorer performance in "Correct Types" (p<0.05), "Correct Money" (p < 0.05) and "Duration" (p < 0.001) compared to HC; and in "Bought Unlisted" (p < 0.05) and "Duration" (p < 0.001) compared to SVD‐CN. However, there was no significant difference between SVD‐CN and HC in VSM variables. In addition, all VSM variables had a discrimination ability with 81% correct classification rate (CCR), 78% sensitivity, and 83% specificity over SVD‐CI and HC. Moreover, "Duration" variables of the VSM was moderately related to composite z‐scores of general cognitive status (r = ‐0.491, p < 0.001), memory (r = ‐0.509, p < 0.001), language (r = ‐0.404, p = 0.001) and visuospatial functions (r =‐0.593, p < 0.001). "Correct Types" (rpb = ‐0.301, p = 0.012) and "Correct Money" (rpb = ‐0.335, p = 0.005) was associated with visuospatial function on SVD groups. Conclusion: This study is the first to evaluate cognitive functions by means of the VSM in SVD in a Turkish speaking population. This study provides encouraging preliminary findings about possibility of the VSM as a tool in the assessment of cognitive impairment and differentiation SVD‐CI from HC.